2014
DOI: 10.1177/0146167214522836
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Bases for Self-Evaluation

Abstract: Several theories propose that self-esteem, or positive self-regard, results from fulfilling the value priorities of one's surrounding culture. Yet, surprisingly little evidence exists for this assertion, and theories differ about whether individuals must personally endorse the value priorities involved. We compared the influence of four bases for self-evaluation (controlling one's life, doing one's duty, benefitting others, achieving social status) among 4,852 adolescents across 20 cultural samples, using an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 51 publications
2
12
0
2
Order By: Relevance
“…For example, multilevel longitudinal research by Christ and colleagues (2014) demonstrated that the context-level effect of intergroup contact on outgroup prejudice was greater than the effect of individual contact. This and similar research demonstrates that collective or contextual processes can influence individual-level processes and outcomes (e.g., Becker et al, 2012, 2014; Thomas et al, 2016). The vast majority of motivational research to date within the SIT literature has focused on motivational influences on individual-level processes (personal and social identity motives).…”
Section: Identity Motives At Different “Levels”supporting
confidence: 60%
“…For example, multilevel longitudinal research by Christ and colleagues (2014) demonstrated that the context-level effect of intergroup contact on outgroup prejudice was greater than the effect of individual contact. This and similar research demonstrates that collective or contextual processes can influence individual-level processes and outcomes (e.g., Becker et al, 2012, 2014; Thomas et al, 2016). The vast majority of motivational research to date within the SIT literature has focused on motivational influences on individual-level processes (personal and social identity motives).…”
Section: Identity Motives At Different “Levels”supporting
confidence: 60%
“…For instance, the personality traits that best predicted well-being were the ones shared within a cultural group, such as extraversion in a culture with high levels of extraversion ( Fulmer et al, 2010 ). Likewise, adolescents’ self-esteem was best predicted by a positive self-evaluation in the domain valued most by others in the culture ( Becker et al, 2014 ). Correspondingly, negative well-being has been related to psychological tendencies that violate the cultural mandate.…”
Section: Discussionmentioning
confidence: 99%
“…To ascertain that modesty reflected cultural rather than personal values (cf. Becker et al, 2014), we compared it with that of punctuality, a characteristic that a Pilot Study verified to be equally important to our Chinese participants at the personal level, but less important at the cultural level.…”
Section: Summary Of Findingsmentioning
confidence: 99%